2011
DOI: 10.1159/000330067
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Immunomodulatory Effects of Bortezomib in Various in vivo Models

Abstract: Bortezomib (Velcade®) is a proteasome inhibitor that has been approved for the treatment of multiple myeloma and mantle cell lymphoma. It has been shown to inhibit the expression of cell adhesion molecules, co-stimulatory molecules, and NFĸB activation, to deplete alloreactive T lymphocytes, and to decrease Th1 cytokine production. The anti-inflammatory effects of bortezomib were further investigated in this current set of studies. Systemic treatment with bortezomib was efficacious in the thioglycolate-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 95 publications
(45 reference statements)
1
17
1
Order By: Relevance
“…Keratinocytes at the site of CD overexpress numerous cytokines and chemokines, such as TNF-α, IFN-γ, MCP-1 and IL-10 (17-19). It has been previously reported that IFN-γ is important in the development of skin hypertrophy, and TNF-α and MCP-1 function as stimulants of immune cell recruitment around blood vessels (17)(18)(19). In the present study, the topical application of MEKS inhibited the histopathological features of CD via suppression of TNF-α, IFN-γ and MCP-1 expression.…”
supporting
confidence: 59%
“…Keratinocytes at the site of CD overexpress numerous cytokines and chemokines, such as TNF-α, IFN-γ, MCP-1 and IL-10 (17-19). It has been previously reported that IFN-γ is important in the development of skin hypertrophy, and TNF-α and MCP-1 function as stimulants of immune cell recruitment around blood vessels (17)(18)(19). In the present study, the topical application of MEKS inhibited the histopathological features of CD via suppression of TNF-α, IFN-γ and MCP-1 expression.…”
supporting
confidence: 59%
“…The identification of the skin as a significant target of Bz is well compatible with the literature. For example, a recent report demonstrated that the topical application of Bz to the skin caused erythema and skin thickening (characteristics of AD) in a murine model of psoriasis . Likewise, proteasome integrity is essentially implicated in preventing misfolded keratins from aggregation, especially in keratin genodermatoses , is important for the regulation of p53 levels in keratinocytes and for the maintenance of keratinocyte contacts through stabilization of desmosomes .…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion rates taken by the PSI System were measured as perfusion units (PU) and calculated by the software PIMsoft (Perimed). Bortezomib (0.005 mg/kg/d) was transdermally administered (20 μl, 1 X/d and 24 h before surgery) in a formulation containing 70.8% propylene glycol, 28.2% water, and 1.0% HPC (w/v), as described by Tung et al (20). After 4 or 7 d on ligation, mice were euthanized and perfused with Ringer solution and zinc fixative.…”
Section: Methodsmentioning
confidence: 99%